Identification of anatomic risk factors for scalar translocation in cochlear implant patients - Eisenhut, Felix; Lang, Stefan; Hölter, Philip; Wiesmüller, Marco; Uder, Michael; Iro, Heinrich; Dörfler, Arnd; Hornung, Joachim; Taha, Lava (Zeitschrift für Medizinische Physik, 2021)
Aim: Microanatomical evaluation of cochlear implant (CI) patients to identify anatomical risk factors for a scalar translocation. Methods: CI patients with both a regular scala tympani spiralization (group A) and a scalar translocation (group B) were identified via postoperative flat-detector computed tomography (FD-CT). Then, the corresponding preoperative multislice computed tomography (MS-CT) and postoperative FD-CT datasets were assessed: First, the cochleae were separated in 6 segments of 45° each. Next, quantitative (cochlea height, length, depth, cochlear duct diameter [CD] per segment; percentual tapering of the CD per segment named cochlear geometry index [CGI]) and qualitative (identifiability of the CI model; CI-integrity; intracochlear array position) parameters were evaluated and compared for both groups. Receiver-operating-characteristics (ROC) analysis was performed for the CGI. Results: In total, 40 preoperative MS-CT and postoperative FD-CT datasets (nA = 20; nB = 20) were analysed. Model “CI 512” was successfully identified and CI-integrity has been confirmed in all cases. Quantitative analysis showed a significant difference of both the CD at 0° (CDA 0°= 2.06 ± 0.23 mm; CDB 0°= 2.19 ± 0.18 mm; p0°= 0.04) and the CGI of the first segment (CGIA 0° -45°= 18.87 ± 6.04%; CGIB 0°-45°= 28.89 ± 8.58%; p0°-45°= 0.0001). For all other 5 cochlear segments there was no significant difference of CD and CGI; there was no significant difference of external cochlea diameters. The area under the curve (AUC) of the CGI0-45° was 0.864 with 24.50° as the optimal cut-off value to discriminate patients with a scala tympani spiralization and a scalar translocation. CGI0-45° of > 24.50° allowed the correct identification of 85% of patients with a scalar translocation. Conclusion: CI insertion trauma is associated with a significantly higher narrowing of the proximal basal cochlea turn (BCT). The CGI as percentual tapering of the BCT turned out as reliable, clinically applicable parameter for identification of patients with an increased risk for a scalar translocation.
CRIS-Team Scopus Importer:2021-03-12
Keywords: anatomical parameters; Cochlear implant; flat-detector computed tomography; insertion trauma; scalar translocation